DESIGN OF BIU RIVER STEEL TRUSS BRIDGE PART WAY BIU-SAMURANGAU MUARA SAMU DISTRICT PASER TANA PASER REGENCY EAST KALIMANTAN PROVINCE - Lulu Assegaf; Markawie Markawie (CERUCUK, 2017)
Samurangau village is located on Muara Samu District, Paser Tana Paser Regency, East Kalimantan Province. Samurangau village has livelihood such as oil palm, farming, and rubber. To make the economy keep going on the people of Samurangau village have to go to the city of Paser Tana Paser regency through Biu village. But the acsess is disconnected by the tributary of Kandilo river, Biu river. Because the exist suspension bridge can only be passed by two-wheeled vehicle and pedestrian, thus it needed bridge enhancement to satisfy the people of Samurangau village. Based on the location, its need the more durability dan it doesn’t need special handling thus the steel truss bridge have been choosen. Based on the difference of elevation thus the different foundation  in each part way is the best selection. Methodology that used in this design refers to the bridge imposition For RSNI T-02-2005 about composite bridge structure design method, refers to RSNI T-03-2005 about Steel Structural Design For Bridge, SNI 03-1729-2002 about Steel Structures Planning Procedures and SNI 03-2847-2002 about Concrete Structures Calculation for Building and SAP2000 software to control allowed tension. In sub-structure of Biu village part way used caisson foundation that qualify to shear stability, bolster stability, and bearing capacity of foundation. In sub-strucure of Samurangau village part way used steel pipe pile that qualify to axial and lateral force.From the planning, structure used the profile of girders are WF 450.300.11.18, WF 900.300.18.34, 2L 180.180.20 for wind truss, WF 400.400.t  for main truss with different thick in each frame. The quality of steel used BJ 55. In sub-structure of Biu village part way used foundation of caisson with its diameter 3,00 m and sub-structure of Samurangau village part way used steel sheet pile with its diameter 0,6 m with quality of steel used BJ 37 with fy 240 MPa and quality of concrete used fc’ 20 MPa. For descrease the soil pressure used box culvert on Samurangau part way.